AB0726 The utility of IGA antiphospholipid antibodies for prediction of thrombotic complications in secondary antiphospholipid syndrome. (23rd January 2014) - Iwaniec, T.A.; Celinska-Lowehoff, M.; Goralczyk, T.; Musial, J.
Abstract : Background: At present we use modified classification criteria (Sydney 2006) for a diagnosis of antiphospholipid syndrome (APS) (1). These criteria do not include IgA class anticardiolipin (aCL) or antiβ2-glycoprotein I (antiβ2GPI) antibodies. However, some data indicate an association of these antibodies with APS obstetrical complications. Moreover, IgA antiβ2GPI antibodies have been associated with thromboembolic events in patients with systemic lupus erythematosus (SLE) (3). Objectives: We assessed a group of APS patients with arterial (stroke, transient ischaemic attack and myocardial infarction) and venous thromboembolic events and/or obstetric complications and their association with antiphospholipid antibody profile. Methods: We enrolled a group of 128 APS patients - 43 with primary (PAPS) and 85 with secondary (SAPS) - into the study. In the SAPS group 74 patients were diagnosed with SLE and 11 – with SLE-like syndrome. ACL and antiβ2-GPI antibodies in 3 classes (IgG, IgM and IgA) were determined using enzyme-linked immunosorbent assay (QUANTA Lite aCL, aβ2GPI ELISA; INOVA Diagnostics, USA). Lupus anticoagulant (LA) was assessed according to SSC 2009 guidelines (4). Statistical analyses were performed using STATISTICA software. Results: We observed a positive correlation between aCL IgA and arterial thrombosis in the SAPS group only (the coefficient of correlation [Phi] =0, 36, p=0, 003). We also observed a weaker correlations between arterial events and LA (Phi=0, 22; p=0, 04) and aCL IgG (Phi=0, 29; p=0, 01). These associations were not found in the PAPS group. Antiβ2-GPI antibodies did not correlate with arterial thrombosis. We did not find any significant correlations between antibodies studied and venous thrombosis, or obstetrical complications. Conclusions: It seems that the evaluation of IgA aCL in addition to IgG and IgM classes might add some information to the thrombotic risk assessment in patients with APS secondary to SLE. References: Miyakis S, Lockshin MD, Atsumi T, et al. International consensus statement on an update of the classification criteria for definite antiphospholipid syndrome (APS). J Thromb Haemost 2006; 4:295-306. Carmo-Pereira S, Bertolaccini ML, Escudero-Contreras A, Khamashta MA, Hughes GRV. Value of anticardiolipin and anti-beta2-glycoprotein I antibody testing in patients with pregnancy morbidity. Ann Rheum Dis 2003; 62: 640-643. Mehrani T, Petri M. Association of IgA Anti-beta2 glycoprotein I with clinical and laboratory manifestations of systemic lupus erythematosus. J Rheumatol 2011; 38: 64-68. Pengo V., Tripodi A., Reber G., Rand T., Ortel L., Galli M., DeGroot P.G. Update of the guidelines for lupus anticoagulant detection. Official communication of the SSC. J Thromb Haemost. 2009; 7: 1737-1740. Disclosure of Interest: None Declared